The way of love - Irigaray, Luce (London : Continuum, 2002)
The Way of Love asks the question: How can we love each other? Here Luce Irigaray, one of the world's foremost philosophers, presents an extraordinary exploration of desire and the human heart.

If Western philosophy has claimed to be a love of wisdom, it has forgotten to become a wisdom of love. We still lack words, gestures, ways of doing or thinking to approach one another as humans, to enter into dialogue, to build a world where we can live together.
Keywords: Love; Sex differences (Psychology); Gender differences; Philosophy; ljubav; spolne razlike; rodne razlike; filozofija